Nonlinear dynamics of the fishbone-induced alpha transport on ITER. (6th October 2020) - Brochard, G.; Dumont, R.; Lütjens, H.; Garbet, X.; Nicolas, T.; Maget, P.
Abstract: The fishbone-induced transport of alpha particles is computed for the ITER 15 MA baseline scenario (ITER Physics Expert Group on Energy Drive 1999 Nucl. Fusion 39 2471) using the non-linear hybrid Kinetic-MHD code XTOR-K. Two limit cases have been studied, in order to analyse the characteristic regimes of the fishbone instability: the weak kinetic drive limit (Berk et al 1999 Phys. Plasmas 6 3102) and the strong kinetic drive limit (Zonca et al 2015 New J. Phys. 17 013052). In both those regimes, characteristic features of the n = m = 1 fishbone instability are recovered, such as a strong up/down-chirping of the mode frequency, associated with a resonant transport of trapped and passing alpha particles. The effects of the n = m = 0 sheared poloidal and toroidal plasma rotation are taken into account in the simulations. The shear is not negligible, which implies that the fishbone mode frequency has a radial dependency, impacting the wave-particle resonance condition. Phase space hole and clump structures are observed in both non-linear regimes, centered around the precessional and passing resonances. These structures remains attached to the resonances as the different mode frequencies chirp up and down. In the non-linear phase, the transport of individual resonant trapped particles is identified to be linked to mode-particle synchronization. On this basis, a partial mechanism for the non-linear coupling between particle transport and mode dominant down-chirping is proposed. The overall transport of alpha particles through the q = 1 surface is of order 2–5% of the initial population between the simulations. The loss of alpha power is found to be directly equal to the loss of alpha particles.